Caribbean and Central American Partnership for Catastrophe Risk Insurance : Pooling Risk to Safeguard against Catastrophes Generated by Natural Events - World Bank (Washington, DC, 2014)
Countries in the Caribbean and Central America are highly vulnerable to the adverse effects associated with earthquakes, tropical cyclones, and other major hydro-meteorological events such as excessive rainfall. Aftermath of disasters typically place significant strain on the fiscal systems of affected countries. Consequently, ministers of the Central American integration system (SICA) and Caribbean community (CARICOM) countries have expressed a strong intention to collectively manage the disaster risk. By understanding the loss potential of disasters caused by natural events and the extent of public intervention in recovery and reconstruction efforts, governments can ascertain their respective contingent liabilities. Sovereign disaster risk financing and insurance can also safeguard against sudden macroeconomic shocks that negatively impact fiscal performance, and in turn, economic development. Caribbean and Central American governments are constrained in their ability to access quick liquidity to absorb fiscal shocks associated with natural hazard impacts because they have limited ability to create contingency funds, and limited capacity for external borrowing. The World Bank in partnership with the United States department of treasury assessed various options, which guided Ministers of Finance of Central America, Panama, and the Dominican Republic (COSEFIN) to identify the Caribbean catastrophe risk insurance facility (CCRIF) as the best option. The CCRIF provides cost-effective and fast-disbursing liquidity, and is an efficient way to finance a liquidity gap arising in the immediate aftermath of disaster.